Aktivitas Antibakteri Ekstrak Etanol Biji Kakao (Theobroma cacao L) Varietas Lindak terhadap Porphyromonas Gingivalis dan Streptococcous mutans - Bernhard Alwien Bremana Pelawi (Fakultas Kedokteran Gigi, 2026)
Oral health problems such as gingivitis and dental caries are strongly associated with pathogenic bacteria, particularly Porphyromonas gingivalis and Streptococcus mutans. The increasing concern regarding the side effects and resistance associated with synthetic antibiotics has encouraged the exploration of natural antibacterial agents. Cocoa beans (Theobroma cacao L.), especially the Lindak variety, contain bioactive compounds such as flavonoids and polyphenols that are known to exhibit antibacterial properties. This study aimed to evaluate the antibacterial activity of ethanol extract of Lindak cacao beans against Porphyromonas gingivalis and Streptococcus mutans. This study used an in vitro experimental laboratory design with the disk diffusion method. The extract was tested at concentrations of 25%, 50%, 75%, and 100%, with chlorhexidine as positive control and sterile distilled water as negative control. Each treatment was performed with four replications (n = 4). The antibacterial activity was evaluated by measuring the diameter of the inhibition zone (mean ± SD, mm). Statistical analysis was conducted using one-way ANOVA followed by Tukey HSD post hoc test with a significance level of p < 0.05. The results showed that the ethanol extract exhibited concentrationdependent antibacterial activity. Against Porphyromonas gingivalis, the inhibition zone diameters were 10.70 ± 0.16 mm (25%), 12.78 ± 0.14 mm (50%), 15.15 ± 0.06 mm (75%), and 17.11 ± 0.10 mm (100%), while the positive control (chlorhexidine) showed 20.83 ± 0.17 mm. Against Streptococcus mutans, the inhibition zone diameters were 11.73 ± 0.18 mm (25%), 13.68 ± 0.12 mm (50%), 15.95 ± 0.11 mm (75%), and 18.34 ± 0.09 mm (100%), compared with 21.53 ± 0.09 mm in the chlorhexidine group. One-way ANOVA demonstrated significant differences among treatment groups (p < 0.05), and the Tukey HSD test confirmed significant pairwise differences between concentrations and controls. In conclusion, the ethanol extract of Lindak cacao beans exhibits significant antibacterial activity against Porphyromonas gingivalis and Streptococcus mutans in a concentration-dependent manner, indicating its potential as a natural antibacterial agent for oral health applications such as mouthwash or toothpaste formulations.
Approved by Teddy
Keywords: Theobroma cacao; Lindak cacao beans; antibacterial activity; Porphyromonas gingivalis; Streptococcus mutans